Pembangunan dan kesihatan alam sekitar - Haliza Abdul Rahman (Kuala Lumpur : Dewan Bahasa dan Pustaka, 2013)
Environmental and public health in Malaysia.
Includes bibliographical references (p. 105-113) and index.
In Malay.
Koleksi sains & teknologi di alam Melayu PATMA
Keywords: Environmental health; Environmental management